2019
DOI: 10.1111/imcb.12224
|View full text |Cite
|
Sign up to set email alerts
|

Murine myeloid‐derived suppressor cells are a source of elevated levels of interleukin‐27 in early life and compromise control of bacterial infection

Abstract: Microbial infections early in life remain a major cause of infant mortality worldwide. This is consistent with immune deficiencies in this population. Interleukin (IL)‐27 is suppressive toward a variety of immune cell types, and we have shown that the production of IL‐27 is elevated in humans and mice early in life. We hypothesize that elevated levels of IL‐27 oppose protective responses to infection during the neonatal period. In this study, we extended previous findings in neonatal mice to identify a populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 48 publications
(170 reference statements)
4
38
0
Order By: Relevance
“…Neonates exhibit elevated levels of IL-27 in the spleen and blood at resting state relative to adults (11, 12). To determine if IL-27 levels continue to rise during infection and how the cytokine may impact the host response, we established a murine model of neonatal sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neonates exhibit elevated levels of IL-27 in the spleen and blood at resting state relative to adults (11, 12). To determine if IL-27 levels continue to rise during infection and how the cytokine may impact the host response, we established a murine model of neonatal sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that MDSCs and macrophages are the dominant cellular sources of IL-27 in neonatal mice in the absence of infection (11, 12). To determine cell types that contribute to the rising IL-27 levels during infection, we profiled cells in the blood and spleens by immunofluorescent labeling and flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations